Pengaruh Sistem Informasi Akuntansi Dan Pengendalian Internal Terhadap Kinerja Perusahaan Pada Pt. Swabina Gatra - Nur Afifah Awaliyah; Umaimah Umaimah (Al-Makki Publisher, 2023)
One of the critical functions carried out by the accounting information system is internal control. Many companies have subpar internal control systems, which might allow employees to commit fraud against the company. The performance is the result of their effort, when employees carry out their task in accordance with their obligation. Thanks to each person's accomplishment, the organization can develop and execute at its best in accordance with its objectives. Improving business performance requires an understanding of how internal controls and financial information systems affect corporate performance and productivity. The goal of this study was to look into and assess the relationship between internal controls and accounting information systems and business success. It's crucial to recognize the factors that influence each of these factors. 30 employees of PT Swabina Gatra made up the study's sample. The test method is multiple linear regression analysis, and PT Swabina Gatra uses a purposive sampling strategy. In this quantitative investigation, the facts that occur in the variables under consideration are explained and presented utilizing methodologies for descriptive data analysis. The results of the study show that while the accounting information system has a positive effect, internal control has a substantial impact on corporate performance. Internal control and accounting information systems fall within the very good category of firm performance, per the results of the research responses from respondents.